Broadband Half Mode Substrate Integrated Waveguide H-plane Horn Antenna - Saeed Fakhte; Mohammadhossein Ashouri (Majlesi Journal of Electrical Engineering, 2023)
A compact, wideband, low cost, high radiation efficiency and planar half mode substrate integrated waveguide (HMSIW) horn antenna is proposed in this work. For the first time, HMSIW is used to design a horn antenna. By using HMSIW waveguide structure instead of Substrate Integrated Waveguide (SIW), the impedance bandwidth of antenna is increased significantly. The use of this waveguide structure in the design of the horn and its feeding system has increased the impedance bandwidth of the antenna. In fact, leaking the electromagnetic waves gradually along the horn increases the bandwidth of antenna. By applying the design equations of the H-plane horn antenna and half mode substrate integrated waveguide, the initial dimensions of the antenna have been obtained, then the best possible solution has been extracted by parametric study and optimization. Simulation results exhibit an impedance bandwidth of 50% from 24GHz to 40GHz. Also, the proposed design shows a gain between 7dB and 10 dB together with radiation efficiency higher than 95% over the frequency band of 25 to 35GHz. The innovation of this work is in providing a new horn structure based on HMSIW with wide impedance bandwidth. In the previously presented works, which are mainly based on SIW, the antenna suffers from a narrow impedance bandwidth.